Perancangan dan Implementasi Aplikasi E-Library Berbasis Web yang Berpusat pada Pengguna: Menuju Perpustakaan Digital yang Lebih Efisien dan Inklusif - Fithry Tahel; Meryance Viorentina Siagian (Universitas Methodist Indonesia, 2026)
Advances in information technology have driven the transformation of library services from conventional systems to more efficient and accessible digital systems. However, digital libraries still face various challenges, such as limited access, a lack of personalized services, and low interoperability and accessibility for users with special needs. This study aims to design and develop a web-based e-library application capable of improving the effectiveness of library management and providing a more adaptive and inclusive information access experience. The methodology used is Design Science Research (DSR), which includes the stages of problem identification, needs analysis through literature review, interviews, and questionnaires, system design using a human-centered design approach, and system prototype development. System design was conducted using Unified Modeling Language (UML) modeling, consisting of use case diagrams, activity diagrams, and class diagrams. The developed system provides user authentication, book search, access to digital resources, and collection and user management by administrators. System testing was conducted using the Black Box Testing method to ensure that every function operates according to specifications. The research results indicate that the developed e-library application is capable of functioning effectively and supports the management of digital libraries more efficiently.